2018
DOI: 10.1113/jp275388
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐dependent potassium channels control proliferation of cardiac progenitor cells and bone marrow‐derived mesenchymal stem cells

Abstract: Endogenous c-Kit cardiac progenitor cells (eCPCs) and bone marrow (BM)-derived mesenchymal stem cells (MSCs) are being developed for cardiac regenerative therapy, but a better understanding of their physiology is needed. Here, we addressed the unknown functional role of ion channels in freshly isolated eCPCs and expanded BM-MSCs using patch-clamp, microfluorometry and confocal microscopy. Isolated c-Kit eCPCs were purified from dog hearts by immunomagnetic selection. Ion currents were barely detectable in fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 84 publications
2
28
1
Order By: Relevance
“…K Ca 3.1 channel, also known as KCNN4, IK Ca and SK4, is an intermediate‐conductance member of the Ca 2+ ‐activated K + channel family and is widely expressed in both excitable and non‐excitable cells, where it plays an important role in various cell functions . Interestingly, there is increasing evidence to support the K Ca 3.1 channel is engaged in MSC proliferation . Previous studies showed that the expression of the K Ca 3.1 channel in human umbilical vein endothelium cells was up‐regulated by fluid flow‐induced shear stress, or its channel activity in vascular smooth muscle cells was enhanced by hypotonic solution‐induced membrane stretch .…”
Section: Introductionmentioning
confidence: 99%
“…K Ca 3.1 channel, also known as KCNN4, IK Ca and SK4, is an intermediate‐conductance member of the Ca 2+ ‐activated K + channel family and is widely expressed in both excitable and non‐excitable cells, where it plays an important role in various cell functions . Interestingly, there is increasing evidence to support the K Ca 3.1 channel is engaged in MSC proliferation . Previous studies showed that the expression of the K Ca 3.1 channel in human umbilical vein endothelium cells was up‐regulated by fluid flow‐induced shear stress, or its channel activity in vascular smooth muscle cells was enhanced by hypotonic solution‐induced membrane stretch .…”
Section: Introductionmentioning
confidence: 99%
“…The article by Vigneault et al . (2018) in this issue of The Journal of Physiology represents one of a few published reports assessing functional expression of ion channels in CPCs.…”
mentioning
confidence: 99%
“…introduced KCa3.1 Ca 2+ ‐dependent K + channels as major contributors to optimizing canine CPC membrane potential and mediating proliferative responses. Interestingly, KCa3.1 channel‐mediated roles in CPCs were also observed in bone marrow‐derived mesenchymal stem cells (BM‐MSCs), a cell population that is widely used in clinical trials for cardiac stem cell therapy (Vigneault et al . 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations